2019
DOI: 10.31219/osf.io/u9yvk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of Phytoplankton and Physico-chemical Parameters in Nursery, Growout and Broodstock Ponds

Abstract: The study measures the relationship between physicochemical variables with the cell density of phytoplankton in different stages of pond – nursery ponds, grow out ponds and brood stock ponds. The study was conducted on nine fish ponds as three from each category of pond at Natore Government Fish Farm in Bangladesh, during the months of January to June in 2012. The observed physicochemical variables– water temperature, transparency, dissolved oxygen, pH, ammonia-nitrogen, total alkalinity and total hardness – w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…and Ulothrix spp. were found as the dominant genera by other researchers (Affan et al., 2005; Begum et al., 2007; Chowdhury et al., 2007; Hossain et al., 2013), which agrees with present study. According to cluster analysis, no significant isolation of phytoplankton genera cleared a constant pattern of the phytoplankton assemblages.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…and Ulothrix spp. were found as the dominant genera by other researchers (Affan et al., 2005; Begum et al., 2007; Chowdhury et al., 2007; Hossain et al., 2013), which agrees with present study. According to cluster analysis, no significant isolation of phytoplankton genera cleared a constant pattern of the phytoplankton assemblages.…”
Section: Discussionsupporting
confidence: 93%
“…The high diversity of phytoplankton was observed in the homestead ponds with variation in dominant genus from station to station for the phytoplankton assemblage. High diversity of phytoplankton was also reported by other researchers (Begum et al., 2007; Chowdhury et al., 2007; Hossain et al., 2013; Khan & Bari, 2019; Khan et al., 2019). The phytoplankton genera such as Aphanizomenon sp., Aphanocapsa sp., Microcystis spp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This agrees with Tas et al [37] in Cernek Lake in Turkey, which may be due to their preference for moderate temperatures, as has been found by other studies [12]. Staurodesmus cuspidatus appeared in location 1 (pH 7.22), which was considered the lowest pH among other locations, while Stichosiphon sansibaricus appeared in summer season (June), which may be returned to increased temperature of water, as mentioned by Hossain et al [38] who reported that Cyanophyta had a positive correlation with the temperature of water in Nursery Lake in Bangladesh. Also, Phacus anacoelus var.…”
Section: Acanthoceras Zachariasiisupporting
confidence: 91%
“…Live organisms of the water consist of several groups and among these, plankton is very important for fish production. Phytoplankton is the basic of primary production of all types of water bodies and is used as food by fish directly or indirectly (Hossain et al, 2013). The microscopic plankton algae of the ponds are critical food for planktivorous fish species (carps) as well as the larvae of commercially important crustaceans and fin fishes.…”
Section: Introductionmentioning
confidence: 99%